Incidence of Ciprofloxacin-Resistant of Methicillin Resistant Staphylococcus aureus isolated from Iraqi patients - Mussa, Ali A.; Al-Mathkhury, Harith Jabbar Fahad (Iraqi Journal of Science, 2018)
The resistance of Staphylococcus aureus to ciprofloxacin has complicated the problem of treating staphylococcal associated infections in which MRSA is the causative agent since ciprofloxacin was the drug of choice to treat such infections. Our study investigated the incidence of Ciprofloxacin resistant S. aureus isolates that were also methicillin resistant among Iraqi patients. The obtained bacterial isolates were tested for Ciprofloxacin resistance using agar dilution method and the sequence of gyrA and parC. The results revealed that about 8% of the isolated MRSA strains were Ciprofloxacin resistant and the resistance was due to mutation in gyrA rather than parC.